2.45 GHz electromagnetic radiation hazard on the rat cortical femur: Morphometric and biomechanical evaluations - Aysegul Akar; Murat Erdem Gultiken; Durmus Bolat; Neslihan Ormanci; Begum Korunur Engiz; Ertugrul Sunan; Ulku Comelekoglu (Medicine Science, 2022)
We aimed to investigate the positive or negative biological effects of Microwave (MW) exposure on rat femur by morphometric analysis and biomechanical test methods. 22 adult rats were separated into two groups: Group first was used as the control group and the second group of rats was used as a study group which was subjected with 2.45 GHz MW frequency for two hours a day for 21 days. Both groups were sacrificed for morphometric and biomechanical evaluation at the end of 21 days. Morphometric properties were measured using Stereo investigator analyzing system programs. In biomechanical measurements, the femurs of control and exposed group rats were evaluated by intrinsic and extrinsic biomechanics properties. Biomechanical measurements were performed from the left femur mid-diaphysis using a three-point bending test. In the morphometrically measurements, significant differences were statistically found (p [Med-Science 2022; 11(2.000): 869-76]